Alien-dominated plant communities' syntopic with seabird's nests: evidence and possible implication from a Mediterranean insular ecosystem. Issue 5 (3rd September 2021) - Battisti, Corrado; Fanelli, Giuliano
Abstract : In a small Mediterranean island (South Sardinia), we compared two non-native plant communities (respectively dominated by Malephora crocea and Mesembrianthemum cristallinum ), located on an insular rocky cliff syntopic with a nesting gull's colony, with a native one (with Limonium sardoum dominant) used as a "control" (without nesting colony). Uni-variate metrics of diversity, Whittaker plot and non-metric multi-dimensional scaling (NMMS) with Morisita distance, evidenced a clear pattern with non-native communities less rich, less even and less diverse, when compared to native assemblage. Limonium native community is probably competitive toward the Malephora community in the absence of gulls but tends to be outcompeted by Malephora in the presence of these seabirds. In this regard, our data suggest a hypothesis that should be tested in future: i.e. those non-native Malephora - and Mesembrynathemum -dominated plant assemblages are favored in those sites where the dropping of gulls creates a nitrophytic environment. Differences in exposition could appear also important to explain the occurrence of the two non-native communities (with Mesembryanthemum crystallinum located along the sea-exposed cliff and Malephora in the internal side, toward the inland).